Effect of hydrofluoric acid and self-etch ceramic primers on the flexural strength and fatigue resistance of glass ceramics: A systematic review and meta-analysis of in vitro studies - Paulo Matias Moreira; Gabriela Luiza Moreira Carvalho; Rodrigo de Castro Albuquerque; Carolina Bosso André (Elsevier, 2024)
This systematic review evaluated the effect of different hydrofluoric acid (HF) etching regimens and a self-etch ceramic primer (SECP) on the flexural strength (FS) and fatigue failure load (FFL) of glass-ceramic materials.The identification of relevant studies was conducted by two authors in five databases: PubMED, Scopus, Web Of Science, LILACS and Virtual Health Library (BVS) until July 2022 with no year limit. The analysis was conducted in RevMan 5.4.1 Software (Cochrane Collaboration) using Random effect model at 5 %. The risk of bias of the included studies were assessed. From the 5349 articles identified, 34 were included for quantitative analysis. Meta-analysis showed that for predominantly glassy ceramics, etching with HF 5 % had no significant impact on FS, however, HF acid etching with concentrations greater than 5 % negatively impacted FS. For lithium disilicate glass-ceramics (LDGC) HF acid etching, negatively influenced FS, while increasing the FFL. HF etching negatively affected FS of hybrid ceramics. The self-etch ceramic primer and HF acid etching showed a similar impact on FFL and FS. This meta-analysis indicates that the impact of SECP and HF acid etching on the mechanical behavior of glass ceramics is material-dependent.